Outer nuclear membrane protein Kuduk modulates the LINC complex and nuclear envelope architecture. - Ding, Z.Y.; Wang, Y.H.; Huang, Y.C.; Lee, M.C.; Tseng, M.J.; Chi, Y.H.; Huang, M.L. (Journal of Cell Biology, 2017)
Linker of nucleoskeleton and cytoskeleton (LINC) complexes spanning the nuclear envelope (NE) contribute to nucleocytoskeletal force transduction. A few NE proteins have been found to regulate the LINC complex. In this study, we identify one, Kuduk (Kud), which can reside at the outer nuclear membrane and is required for the development of Drosophila melanogaster ovarian follicles and NE morphology of myonuclei. Kud associates with LINC complex components in an evolutionarily conserved manner. Loss of Kud increases the level but impairs functioning of the LINC complex. Overexpression of Kud suppresses NE targeting of cytoskeleton-free LINC complexes. Thus, Kud acts as a quality control mechanism for LINC-mediated nucleocytoskeletal connections. Genetic data indicate that Kud also functions independently of the LINC complex. Overexpression of the human orthologue TMEM258 in Drosophila proved functional conservation. These findings expand our understanding of the regulation of LINC complexes and NE architecture.